NORMALIZATION OF DIPLOMATIC RELATIONS BETWEEN THE U.S. AND CUBA 2014-2015 - Raviq Ayusi (HI 15 UMY 413, 2015)
*413 The US government has currently taken a decision to normalize diplomatic relations with Cuba. Cuba is one of the countries that is imposed by the US foreign policy through sanctions in the form of diplomatic disengagement and economic embargo. This decision is intended to chart a new course in the US and Cuba relation. The approach has been taken since President Obama took office in 2009. The consideration is the outdated approach that has been going for five decades has failed to advance the US interest. The new step tends to aim at supporting Cuban people to determine future of their country. The aims of this research is intended to look more for the factors behind the decision making that encourages the US intention to normalize the diplomatic relation with Cuba. The method of research puts the US foreign policy as a unit of analysis and the USCuba relation as a unit of explanation. This research is based on the information that is collected from the early Obama administration in 2009, exactly in the second period of Obama administration in end of last year, 2014. The US foreign policy decision to normalize diplomatic relation will be analyzed by using the theory of the foreign policy decision-making process by William D. Coplin. Finally, the decision making in normalization between the US and Cuba is because of Obama’s ideology of pragmatism. Obama brings the term of change and prefers to do engagement. In addition, normalization with Cuba is supported by the US condition. By seeing the US condition through foreign policy decisionmaking process by William D. Coplin, there are three determinants: domestic politic, economy and military capabilities, and international context. The main result shows that the most influential factors in the taking decision of normalization are because of Obama’s ideology of pragmatism and the US condition. Keywords: Obama, The US Policy, Cuba, The US and Cuba relation, and the normalization of diplomatic ties.